2022
DOI: 10.3390/su141811478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Machine Learning Algorithm on Drinking Water Quality for Better Sustainability

Abstract: Water has become intricately linked to the United Nations’ sixteen sustainable development goals. Access to clean drinking water is crucial for health, a fundamental human right, and a component of successful health protection policies. Clean water is a significant health and development issue on a national, regional, and local level. Investments in water supply and sanitation have been shown to produce a net economic advantage in some areas because they reduce adverse health effects and medical expenses more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…It was stated that KNN in terms of precision, LASSO LARS (LL), Stochastic Gradient Descent (SGD) in terms of recall, SVM, and Artificial Neural Network (ANN) in terms of ROC curve/AUC were good classifiers. Although XGB was used in the study, it was reported to give moderate results (Kaddoura, 2022). Nasir et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that KNN in terms of precision, LASSO LARS (LL), Stochastic Gradient Descent (SGD) in terms of recall, SVM, and Artificial Neural Network (ANN) in terms of ROC curve/AUC were good classifiers. Although XGB was used in the study, it was reported to give moderate results (Kaddoura, 2022). Nasir et al.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is necessary to further strictly control the maintenance of infrastructure, such as through the supervision of pipe networks and related technical indicators [36,69], to ensure that the water demand of the vast number of users is met. Third, attention should be paid to improving the efficiency of capital use and not blindly investing too much money in maintaining the pipe network infrastructure because there is no obvious relationship between the qualified rate of pipe network pressure and scale efficiency [70]. The water industry cannot expand its scale without limit but should control the scale of expansion within a reasonable range and focus on improving management efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve MLPNN-based models were evaluated for performance in the training and validation process with accuracy (Acc), precision (Prec), sensitivity (Sens), F1-score, and MAE. These efficiencies were formulated from ( 16) to (19) [38], [39], [40].…”
Section: Model Evaluationmentioning
confidence: 99%
“…During the training process, the categorical crossentropy loss was used to evaluate the model's efficiency for multi-class in neural networks, which is formulated in (20) [40].…”
mentioning
confidence: 99%